Invasive lobular breast carcinoma metastatic to the colon: a case report of a rare condition and its challenges - Carlos Eduardo Rodrigues; Letícia Morais Sermoud; Maria Fátima Gaui; José Ricardo Souza (Brazilian Journal of Oncology)
The most common sites for metastatic breast neoplasm are the bones, lungs, liver, and central nervous system. Metastases to the gastrointestinal tract are rare and especially involve the stomach, more than to the colon. The clinical and radiological presentation of the metastatic disease usually does not aid in making the differential diagnosis between primary neoplastic lesions of the colon or rectum and metastases from breast cancer. This often results in inadequate initial treatment. The clinical, radiological and histopathological diagnoses are challenging, and immunohistochemical analyses become necessary in most cases. Therefore, publication in the medical literature of more cases like this one should be stimulated, with the aim of gaining more data on treatments that are used and hence to clarify what the best approach is, focusing especially on better quality of life and survival for these patients.